Localization of the ventricular pacing site from BSPM and standard 12-lead ECG: a comparison study - Sedova, Ksenia A; van Dam, Peter M; Blahova, Marie; Necasova, Lucie; Kautzner, Josef (Scientific reports, 2023)
Inverse ECG imaging methods typically require 32-250 leads to create body surface potential maps (BSPM), limiting their routine clinical use. This study evaluated the accuracy of PaceView inverse ECG method to localize the left or right ventricular (LV and RV, respectively) pacing leads using either a 99-lead BSPM or the 12-lead ECG. A 99-lead BSPM was recorded in patients with cardiac resynchronization therapy (CRT) during sinus rhythm and sequential LV/RV pacing. The non-contrast CT was performed to localize precisely both ECG electrodes and CRT leads. From a BSPM, nine signals were selected to obtain the 12-lead ECG. Both BSPM and 12-lead ECG were used to localize the RV and LV lead, and the localization error was calculated. Consecutive patients with dilated cardiomyopathy, previously implanted with a CRT device, were enrolled (n = 19). The localization error for the RV/LV lead was 9.0 [IQR 4.8-13.6] / 7.7 [IQR 0.0-10.3] mm using the 12-lead ECG and 9.1 [IQR 5.4-15.7] / 9.8 [IQR 8.6-13.1] mm for the BSPM. Thus, the noninvasive lead localization using the 12-lead ECG was accurate enough and comparable to 99-lead BSPM, potentially increasing the capability of 12-lead ECG for the optimization of the LV/RV pacing sites during CRT implant or for the most favorable programming.
Keywords: prostředky srdeční resynchronizační terapie; Cardiomyopathy, Dilated; srdeční resynchronizační terapie; Humans; lidé; Electrodes; elektrokardiografie; Cardiac Resynchronization Therapy; dilatační kardiomyopatie; elektrody; Cardiac Resynchronization Therapy Devices; Electrocardiography